PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN PEMAHAMAN KEBERAGAMAAN DALAMPEMBELAJARAN PAI DI SMAN 30 JAKARTA - Ismi Farah Azizah; Muhamad Ariz Hibrizi, Aulawia Hidayati, Rio Permata Hati (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2025)
This research aims to develop interactive learning media that is effective in increasing students' understanding of religious diversity in Islamic Religious Education (PAI) subjects at the high school level. Using research and development (R&D) methods with the ADDIE (Analyze, Design, Develop, Implement, Evaluate) model, this research produced a word search-based educational game called "Word of Wonder" (WOW). This game is designed to actively and interactively involve students in the learning process, so it is expected to improve the quality of PAI learning and encourage students to better understand and internalize religious values. The results of the trial show that this interactive learning media is effective in increasing student engagement and understanding of PAI material. The development of this learning media is expected to be an innovative alternative in the PAI teaching method in high schools.